Opposing Catecholamine Changes in the Bed Nucleus of the Stria Terminalis during Intracranial Self-Stimulation and its Extinction - Park, Jinwoo (2012)
BACKGROUND: While studies suggest that both dopamine and norepinephrine neurotransmission support reinforcement learning, the role of dopamine has been emphasized. As a result, little is known about norepinephrine signaling during reward learning and extinction. Both dopamine and norepinephrine projections innervate distinct regions of the bed nucleus of the stria terminalis (BNST), a structure that mediates behavioral and autonomic responses to stress and anxiety. We investigated whether norepinephrine release in the ventral (v) BNST and dopamine release in the dorsolateral (dl) BNST correlate with reward learning during intracranial self-stimulation (ICSS). METHODS: Using fast-scan cyclic voltammetry, norepinephrine concentration changes in the vBNST (n = 12 animals) during ICSS were compared to dopamine changes in the dlBNST (n = 7 animals) and nucleus accumbens (NAc) (n = 5 animals). Electrical stimulation was in the ventral tegmental area/substantia nigra region. RESULTS: Whereas dopamine release was evoked by presentation of a cue predicting reward availability in both dlBNST and NAc, cue-evoked norepinephrine release did not occur in the vBNST. Release of both catecholamines was evoked by the electrical stimulation. Extracellular changes in norepinephrine were also studied during extinction of ICSS and compared to results obtained for dopamine. During extinction of ICSS norepinephrine release in the vBNST occurred at the time where the stimulation was anticipated whereas dopamine release transiently decreased. CONCLUSIONS: The data demonstrate that norepinephrine release in the vBNST differs from dopamine release in the dlBNST and the NAc in that it signals the absence of reward rather than responding to reward predictive cues.